(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A decade ago, global data began to climb exponentially. It is primarily aggregated through the worldwide web, including social networks, multimedia files, web search requests, text messages, devices and sensors for the Internet of Things. In extracting useful data from such a large volume of data, there are many difficulties. With the emergence of Widespread & Ubiquitous Computing, the term context awareness is becoming popular. Using context data such as physical context, computational context, and user context/tasks, the context-sensitive systems collect data and modify system actions accordingly. The key purpose of this article is to focus on how such large volumes of data are treated by context-sensitive computing systems. In a satellite navigation device, for example, the user’s current position is the reference used to change the visualization automatically (for example. map, arrows, direction etc.). From a Big Data perspective, this paper discusses context-aware computing systems and examines numerous big data challenges